16.7%-efficiency ternary blended organic photovoltaic cells with PCBM as the acceptor additive to increase the open-circuit voltage and phase purity. Issue 36 (27th August 2019) - Pan, Ming-Ao; Lau, Tsz-Ki; Tang, Yabing; Wu, Yi-Ching; Liu, Tao; Li, Kun; Chen, Ming-Chou; Lu, Xinhui; Ma, Wei; Zhan, Chuanlang
Abstract : Ternary solar cells with an efficiency of 16.7% were enabled through the use of PCBM as a higher LUMO-level acceptor additive to concurrently increase V oc, J sc and FF values. Abstract : The field of organic photovoltaics (OPVs) has seen rapid development in the past few years, particularly, with reports on the use of a high performance nonfullerene electron acceptor (named Y6) in binary devices. In this paper, we demonstrate a simple yet effective ternary approach that can simultaneously increase the open-circuit voltage, short-circuit current-density, and fill factor of a binary device based on Y6 and a donor polymer named PM6. By adding a small amount of PCBM into the PM6:Y6 system, we achieved a high efficiency of 16.7%, which is the best value reported for an OPV device to date. Importantly, this ternary material approach has wide-ranging applicability, as we demonstrated the same beneficial effects in multiple systems, including PM6:IT-4F, PM7:IT-4F, PM6:Y6, and PM7:Y6. The LUMO energy (−3.9 eV) of PCBM lies between the LUMO (−3.6 eV) of PM6/PM7 and the LUMO (−4.1 eV) of IT-4F/Y6, which is one reason for the increased V oc . After blending with PCBM, the homogenous fine-film morphology and the π–π stacking patterns of the host binary structure are maintained, while the phase purity is increased, the hole and electron mobilities are increased, and monomolecular recombination is reduced, all of which, plus the visible absorption of PCBM, are the reasons for the concurrently improved fill-factor and increased short-circuit current density. This approach can be used in other OPV systems and should have wide applicability.